Calcyphosine promotes the proliferation of glioma cells and serves as a potential therapeutic target. Issue 4 (6th September 2021) - Zhu, Zheng; Wang, Jiao; Tan, Juan; Yao, Yue‐Liang; He, Zhi‐Cheng; Xie, Xiao‐Qing; Yan, Ze‐Xuan; Fu, Wen‐Juan; Liu, Qing; Wang, Yan‐Xia; Luo, Tao; Bian, Xiu‐Wu
Abstract: Calcyphosine (CAPS) was initially identified from the canine thyroid. It also exists in many types of tumor, but its expression and function in glioma remain unknown. Here we explored the clinical significance and the functional mechanisms of CAPS in glioma. We found that CAPS was highly expressed in glioma and high expression of CAPS was correlated with poor survival, in glioma patients and public databases. Cox regression analysis showed that CAPS was an independent prognostic factor for glioma patients. Knockdown of CAPS suppressed the proliferation, whereas overexpression of CAPS promoted the proliferation of glioma both in vitro and in vivo . CAPS regulated the G2/M phase transition of the cell cycle, but had no obvious effect on apoptosis. CAPS affected PLK1 phosphorylation through interaction with MYPT1. CAPS knockdown decreased p‐MYPT1 at S507 and p‐PLK1 at S210. Expression of MYPT1 S507 phosphomimic rescued PLK1 phosphorylation and the phenotype caused by CAPS knockdown. The PLK1 inhibitor volasertib enhanced the therapeutic effect of temozolomide in glioma. Our data suggest that CAPS promotes the proliferation of glioma by regulating the cell cycle and the PLK1 inhibitor volasertib might be a chemosensitizer of glioma. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.